Pelatihan Penggunaan Reference Manager Mendeley bagi Mahasiswa Program Studi Pendidikan Bahasa Inggris UKI Toraja - Markus Deli Girik Allo; Eka Prabawati Rum; Ilmiah Ibrahim (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
In general, there are still many academics who do citations manually so that they do not show proper citation consistency. In training the use of reference managers at the UKI Toraja English Education Study Program, the application used was Mendeley. After implementing the training on using the Mendeley application reference manager, the authors can conclude that student participants are able to create a Mendeley account and install, install Plugins for Microsoft Office Word, install Plugins for Web Browsers, use Mendeley applications, add references from files, add manual references, add references from the Web Browser, change reference details, add citations to documents, add bibliography, add citation styles, and change citation styles. Thus, through this training, in addition to strengthening the use of the Mendeley application in writing scientific papers, it is also a hope in the future so that students can produce quality scientific works.